2021
DOI: 10.1016/j.asmr.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Arthrography in Rugby Players Undergoing Shoulder Stabilization for Glenohumeral Instability: Professionals Have Higher Frequencies of More Pathologies

Abstract: Purpose: To quantify the magnetic resonance arthrography (MRA) findings in rugby players during preoperative workup for anterior surgical stabilization for glenohumeral instability. Methods: All patients who underwent glenohumeral instability surgery in our institution between 2008 and 2018 were considered for inclusion. Rugby players were identified using the patient's medical notes, with subsequent identification of all professional players. All rugby player's preoperative MRA findings were recorded and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Preoperative decision-making in relation to choice of surgical intervention was made on a patient-by-patient basis, with numerous factors being considered, including (1) magnetic resonance arthrography findings including (a) percentage of glenoid bone loss, as well as (b) concomitant injury to both the humeral head and the glenoid labrum; (2) patient instability status (high- vs. low-performance athletes, or those whom suffer from primary or recurrent instability), and (3) patient preference. 1 , 6 …”
Section: Methodsmentioning
confidence: 99%
“…Preoperative decision-making in relation to choice of surgical intervention was made on a patient-by-patient basis, with numerous factors being considered, including (1) magnetic resonance arthrography findings including (a) percentage of glenoid bone loss, as well as (b) concomitant injury to both the humeral head and the glenoid labrum; (2) patient instability status (high- vs. low-performance athletes, or those whom suffer from primary or recurrent instability), and (3) patient preference. 1 , 6 …”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] Recurrent instability is not without morbidity, with each dislocation episode resulting in increasing glenoid bone loss. 5,6 Although a myriad of management options exist, the open Latarjet (OL) procedure has emerged as the procedure of choice for many, with recent consensus guidelines recommending its use in cases of recurrent shoulder instability in patients with >15% glenoid bone loss. [7][8][9][10][11] The OL procedure has previously been reported to result in excellent clinical outcomes in the short term, with high rates of return to play (RTP) and low recurrence rates at medium-term follow-up, 10,[12][13][14][15][16][17] with the procedure being increasingly performed using an arthroscopic technique.…”
Section: Introductionmentioning
confidence: 99%
“…14 Recurrent instability is not without morbidity, with each dislocation episode resulting in increasing glenoid bone loss. 5,6 Although a myriad of management options exist, the open Latarjet (OL) procedure has emerged as the procedure of choice for many, with recent consensus guidelines recommending its use in cases of recurrent shoulder instability in patients with >15% glenoid bone loss. 711…”
Section: Introductionmentioning
confidence: 99%
“…8 The complexity of the anatomic shoulder stabilizers results in a variety of pathologies in patients with anterior shoulder instability. 3,10,13,14,20,25 Davey et al 5,6 previously reported that the average collision athlete with anterior shoulder instability experiences a multitude of pathologies secondary to recurrent dislocations displayed on preoperative imaging before surgical stabilization, with bony Bankart and Hill-Sachs lesions being the most common. In addition, the humeral avulsion glenohumeral ligament (HAGL) lesion has been shown to occur in up to 10% of cases of recurrent anterior shoulder instability.…”
mentioning
confidence: 99%